(untitled) (Medical Forum Monthly, 2021)
Objective: To determine the visual acuity in keratoconus patient after the contact lens implantation through cross corneal linkage process. Study Design: Experimental study. Place and Duration of Study: This study was conducted at the Cornea clinic, Isra Postgraduate Institute of Ophthalmology, Al-Ibrahim Eye Hospital, Karachi from January 2019 to August 2019. Materials and Methods: 74 patients with progressive keratoconus of age 12 years to 40 years, central corneal thickness more than 400microns and without prior history of CXL corneal procedure were included in the study. Preoperative assessment was based on history, examination and investigations. Operative procedure was performed and postoperative assessment of visual outcomes and complications were noted. Statistical analysis was done by SPSS version 20. Results: Statistically significant difference at p-value <0.001 of Best corrected visual acuity with contact lens (BCVACL) was observed in 93.2% of the patients with 6/6 visual acuity at 3rd month follow up after the contact lens implantation through corneal cross linkage. Conclusion: Significant improvement observed in the visual acuity, Best Corrected Visual Acuity with Contact Lens (BCVACL) of keratoconus patient treated with corneal cross-linkage process with no complications.